Deciphering Financial Indicators: Analyzing the Role of Current Ratio, Debt to Equity Ratio, and Net Profit Margin in Shaping Stock Prices of Pharmaceutical Companies on the Indonesian Stock Exchange (2020-2022) - Mujiyani; Sri Sapto Darmawati; Widio Purwani; Mulatsih (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
This study was designed to assess how the current ratio, debt to equity ratio, and net profit margin affect the stock prices of pharmaceutical firms listed on the Indonesian stock exchange from 2020 to 2022. Seven companies were chosen using purposive sampling for this analysis. The study was based on secondary data, such as the firms' annual financial reports and stock prices. A multiple linear regression approach was used for the analysis. It was found that the current ratio and net profit margin have a significant effect on stock prices individually, but the debt to equity ratio does not. When considered together, however, the current ratio, debt to equity ratio, and net profit margin do have a significant combined effect on stock prices.